The Open Access Citation Advantage: Does It Exist and What Does It Mean for Libraries? - Lewis, Colby Lil (Information Technology and Libraries, 2018)
The last literature review of research on the existence of an Open Access Citation Advantage (OACA) was published in 2011 by Philip M. Davis and William H. Walters. This paper reexamines the conclusions reached by Davis and Walters by providing a critical review of OACA literature that has been published 2011, and explores how increases in OA publication trends could serve as a leveraging tool for libraries against the high costs of journal subscriptions.